Perform tumor-specific survival analysis for Merkel cell carcinoma patients undergoing surgical resection based on the SEER database by constructing a nomogram chart - Zhou Jingxuan; Yu Hai; Xia Xichun; Chen Yanan; Ming Wai-kit; Jiang Yuzhen; Lak Yau Sun; Ip Chongchong; Huang Chaodi; Zhao Qiqi; Zheng Suzheng; Xia Liming; et al. (Open Medicine)
To explore the postoperative risk factors of Merkel cell carcinoma patients who have undergone surgical resection, and to construct a survival prognosis column chart.